Efficacy of naloxone in reducing postictal central respiratory dysfunction in patients with epilepsy: study protocol for a double-blind, randomized, placebo-controlled trial. Issue 1 (December 2016) - Rheims, Sylvain; Valton, Luc; Michel, Véronique; Maillard, Louis; Navarro, Vincent; Convers, Philippe; Bartolomei, Fabrice; Biraben, Arnaud; Crespel, Arielle; Derambure, Philippe; de Toffol, Bertrand; Hirsch, Edouard; et al.
Abstract Background Generalized tonic-clonic seizures (GTCSs) are the main risk factor for sudden unexpected death in epilepsy (SUDEP). Experimental and clinical data strongly suggest that the majority of SUDEP results from a postictal respiratory dysfunction progressing to terminal apnea. Postictal apnea could partly derive from a seizure-induced massive release of endogenous opioids. The main objective of this study is to evaluate the efficacy of an opioid antagonist, naloxone, administered in the immediate aftermath of a GTCS, in reducing the severity of the postictal central respiratory dysfunction. Methods/design The Efficacy of Naloxone in Reducing Postictal Central Respiratory Dysfunction in Patients with Epilepsy (ENALEPSY) study is a multicenter, double-blind, randomized, placebo-controlled trial conducted in patients with drug-resistant focal epilepsy who are undergoing long-term video-electroencephalogram (EEG) monitoring (LTM) in an epilepsy monitoring unit (EMU). We plan to randomize 166 patients (1:1) to receive intravenous naloxone (0.4 mg) or placebo in the immediate aftermath of a GTCS. Because inclusion in the study needs to take place prior to the occurrence of the GTCS, and because such occurrence is observed in about one-fourth of patients undergoing LTM, we plan to include a maximum of 700 patients upon admission in the EMU. The primary endpoint will be the proportion of patients whose oxygen saturation is <90 % between 1 and 3 min after the end of a GTCS. Secondary outcomes will include the following: the proportion of patients who show postictal apnea, the occurrence and duration of postictal generalized EEG suppression, the total duration of the postictal coma, postictal pain, and the number of patients who have a second GTCS within 120 min after the intravenous injection. Discussion The demonstration of naloxone's efficacy on the severity of postictal hypoxemia will have two primary consequences. First, naloxone would be the first and only therapeutic approach that could be delivered immediately to reverse postictal apnea. Second, demonstration that an opioid antagonist can effectively reduce postictal apnea would pave the way for an assessment of a preventive therapy for SUDEP targeting the same pathophysiological pathway using oral administration of naltrexone. Trial registration ClinicalTrials.gov identifier:NCT02332447 . Registered on 5 January 2015.